2013
DOI: 10.1016/j.ydbio.2013.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of Eya1/Six1 disrupts the saccular phase of lung morphogenesis and causes remodeling

Abstract: The Eya1 gene encodes a transcriptional co-activator that acts with Six1 to control the development of different organs. However, Six1-Eya1 interactions and functional roles in mesenchymal cell proliferation and differentiation as well as alveolarization during the saccular stage of lung development are still unknown. Herein, we provide the first evidence that Six1 and Eya1 act together to regulate mesenchymal development as well as alveolarization during the saccular phase of lung morphogenesis. Deletion of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…The Hh signalling pathway is a prominent regulator of embryonic development, where Hh ligands function as morphogens to control numerous developmental processes12. Interestingly, in Drosophila eye development, hh is a direct target of sine oculis (the homologue of Six1)13 and Six1 regulates Hh/GLI signalling during lung development and in fibroblasts1415. In addition, Twist1 and Hh/GLI signalling are intimately linked during development16, and recently Twist1 and Snail1 were associated with the Hh pathway in tumour-initiating cells1718.…”
mentioning
confidence: 99%
“…The Hh signalling pathway is a prominent regulator of embryonic development, where Hh ligands function as morphogens to control numerous developmental processes12. Interestingly, in Drosophila eye development, hh is a direct target of sine oculis (the homologue of Six1)13 and Six1 regulates Hh/GLI signalling during lung development and in fibroblasts1415. In addition, Twist1 and Hh/GLI signalling are intimately linked during development16, and recently Twist1 and Snail1 were associated with the Hh pathway in tumour-initiating cells1718.…”
mentioning
confidence: 99%
“…Eyes absent1 (EYA1) and sine oculis1 (SIX1), two homeobox transcriptions factors involved in eye development and expressed in lung epithelium and mesenchyme, were also found to affect lung development (116)(117)(118). Both Six1 -/-and Eya1 -/-lungs show a hypoplastic phenotype with branching defects, which is exaggerated in Six1 -/-;Eya1 -/-mutants.…”
Section: Lessons From Functional Inhibition and Overexpression Of Hh mentioning
confidence: 99%
“…Specifically, decreased EYA1 and SIX1 expression during the late pseudoglandular stage involving epithelial branching and distal airway maturation led to the pulmonary hypoplasia (PH) [5]. Transgenic mouse model demonstrated that deletion of either Six1 or Eya1 genes leads to a defect of mesenchymal cell development and remodeling of the distal lung septae and arteries [6]. It has been proved that EYA1 and SIX1 played pivotal roles during lung morphogenesis [7].…”
Section: Backgroundsmentioning
confidence: 99%